Family Compliance With Counseling for Children Traveling to the Tropics. Issue 3 (8th March 2013) - Caillet‐Gossot, Stéphanie; Laporte, Rémi; Noël, Guilhem; Gautret, Philippe; Soula, Georges; Delmont, Jean; Faucher, Benoit; Parola, Philippe; Osei, Lindsay; Minodier, Philippe
Abstract : Background: The number of people, both adults and children, traveling abroad, is on the rise. Some seek counseling at travel medicine centers before departure. Methods: A prospective study was conducted among children <16 years visiting a travel medicine center in Marseille, France, from February 2010 to February 2011. Parents were contacted by telephone 4 weeks after their return, and asked about compliance with pre‐travel advice. Results: One hundred sixty‐seven children were evaluated after their trip. Compliance with immunizations, malaria chemoprophylaxis, and food‐borne disease prevention was 71, 66, and 31%, respectively. Compliance with malaria chemoprophylaxis varied significantly with destination, and was higher for African destinations. Significant features associated with poor compliance with chemoprophylaxis were a trip to Asia or the Indian Ocean, age <5 years, and a monoparental family. Compliance with prevention of food‐ and water‐borne diseases was higher in children < 2 years of age. Conclusions: A ≥80% compliance with pre‐travel counseling in children traveling overseas was achieved only for drinking bottled water, using repellents, a routine vaccine update, and yellow fever immunization.